PHENOTYPIC, CYTOGENETIC AND MOLECULAR ANALYSIS OF INTERSPECIFIC RAPESEED HYBRIDS (Experimental biology, 2026)
Rapeseed (Brassica napus L.) is a key oilseed crop, the value of which is determined by both yield and oil quality. In this study, doubled haploid (DH) interspecific hybrid lines of rapeseed × turnip (B. napus × B. rapa) was evaluated using an integrated approach including phenotypic analysis, cytogenetics, and molecular markers. Phenotypic evaluation revealed significant diversity in key quantitative traits, such as seed weight per plant, pod number, and thousand-seed weight, with heterosis evident in some lines. Early flowering of the hybrids compared to the parental forms indicates the influence of genomic interactions on plant development. Cytogenetic analysis using FISH and GISH confirmed the presence of chromosomes from both parents, revealing segments of introgression and signs of genomic stability after chromosome doubling. Molecular studies using SSR markers revealed high polymorphism and the presence of alleles introgressed from B. rapa, consistent with cytogenetic data. Analysis of the seed fatty acid composition revealed increased oleic acid content and low erucic acid levels, which meets modern oil quality requirements. These results demonstrate the effectiveness of combining interspecific hybridization and DH technology for identifying favorable allelic combinations that enhance the breeding value of lines. These lines may serve as promising material for improving the yield and quality of rapeseed oil.
Keywords: canola, doubled haploid, SSR markers, B. napus, B. rapa, tolerance